Importance of urbanized wetlands environments in the reproduction of avifauna, city of Martil (Region of Tetouan) in Morocco - Mars Naima; Maouni Abdelfattah; Saïdi Rabah (E3S Web of Conferences, 2023)
This study focused on the significance of urban and peri-urban wetlands in the Martil plain of Tetouan, Morocco, for bird reproduction. Conducted over a two-year period, the research employed fixed-site counting and weekly visits to assess reproductive indicators such as chicks, nests, courtship displays, and territorial defense. The findings demonstrated that these wetland environments play a vital role in the reproduction of 37 bird species from 15 families, including species of national importance, declining Mediterranean species, vulnerable species according to the IUCN, and rare breeding species. These results underscore the critical importance of conserving and sustainably managing these wetland areas. By prioritising the preservation of urban and peri-urban wetlands, Morocco can contribute to global biodiversity conservation efforts while addressing the challenges of urbanization and climate change